2019
DOI: 10.1177/1359104519838571
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parental attitudes toward children with primary headaches

Abstract: There is a lack of data on parental attitudes toward children with primary headaches. The aim of this study is to determine whether there is a relationship between primary headaches and parental attitudes in the pre-adolescent pediatric population. In this cross-sectional study, 195 children with primary headache and 43 healthy children aged 9–16 years were included. A questionnaire for sociodemographic variables, visual analog scale (VAS), Social Anxiety Scale and Depression Inventory for Adolescents and Chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…The findings of these studies support our findings. Ertem et al (15) observed that the authoritarian-repressive behavior pattern was more common in mothers of children with pre-adolescent migraine. These findings correspond to the inadequate control of family behaviors in the parents of children with headaches in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of these studies support our findings. Ertem et al (15) observed that the authoritarian-repressive behavior pattern was more common in mothers of children with pre-adolescent migraine. These findings correspond to the inadequate control of family behaviors in the parents of children with headaches in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature there are very few studies that have involved both parents in assessing their child's headache. In a study conducted by Ertem et al both parents were included in assessing headache characteristics, depression, anxiety, and parental attitudes in the pediatric population with episodic migraine (EM), CM, and TTH 15 . In regard to psychological problems, pain intensity had a statistically significant positive correlation in all three groups.…”
Section: The Role Of Parents On Children Headachementioning
confidence: 99%
“…Among the environmental factors that can affect the onset and maintenance of headaches in children and adolescents, the role of parents’ behavior seems to be relevant, although it has not yet been deeply studied 15 . In fact, elements such as emotional regulation, attachment, and educational styles, and the presence of dysfunctional coping styles and psychopathologies in mothers, can negatively affect headache in children .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that parents of chronic migraine patients have higher oppressive-authoritarian attitudes than those of patients with other types of headache [14], and are more sensitive and overprotective regarding their children's health problems [15]. Higher age of patients was associated with negative parenting styles [14,16,17]. Previous studies on the relationship between headache characteristics and parenting attitudes have shown that the ambivalent attachment style was associated with high attack frequency and pain intensity in children with migraine [18].…”
Section: Introductionmentioning
confidence: 98%
“…There are few studies on parenting attitudes toward children with migrainous headaches. Studies have shown that parents of chronic migraine patients have higher oppressive-authoritarian attitudes than those of patients with other types of headache [14], and are more sensitive and overprotective regarding their children's health problems [15]. Higher age of patients was associated with negative parenting styles [14,16,17].…”
Section: Introductionmentioning
confidence: 99%